Thermoelectric conversion element, thermoelectric conversion module, wideband image sensor, and method for manufacturing thermoelectric conversion element
Patent Information
- Application Number
- JP2023122658
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-27
- Publication Date
- 2025-02-06
AI Technical Summary
【0021】 本発明によれば、薄膜化が容易であり、かつ物理的な強度や耐久性に優れた熱電変換素子、熱電変換モジュール、広帯域イメージセンサー、および熱電変換素子の製造方法を提供することができる。
Smart Images

Figure 2025018705000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoelectric conversion element, a thermoelectric conversion module, a wideband image sensor, and a method for manufacturing a thermoelectric conversion element. [Background technology]
[0002] In recent years, power sources that use EH (Energy Harvesting) technology, which utilizes energy from everyday life, have been attracting attention as a sustainable power source that supports IoT (Internet of Things) technology. One of the power generating elements used in such power sources is a thermoelectric conversion element. Thermoelectric conversion elements are elements that utilize the "Seebeck effect," which states that a voltage is generated when a temperature difference is created between both ends of a material, and are usually constructed by combining n (negative) type thermoelectric conversion materials and p (positive) type thermoelectric conversion materials.
[0003] Here, as one of the thermoelectric conversion materials forming the thermoelectric conversion element, fibrous carbon nanostructures such as carbon nanotubes (hereinafter, also simply referred to as "CNTs") are used because they have excellent electrical conductivity and can be controlled to be n-type or p-type by doping materials. It is known that CNTs are n-type when produced, but are oxidized and revert to p-type when exposed to the atmosphere. Therefore, a technique has been proposed for maintaining CNTs as n-type by doping them with organic materials (see, for example, Patent Documents 1-2 and Non-Patent Documents 1-3). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 5768299 [Patent Document 2] Patent No. 6340077 [Non-patent literature]
[0005] [Non-Patent Document 1] Y. Nonoguchiet.al., Chem. Asian J. 13 (2018) 3942-3946. [Non-Patent Document 2] Y. Nonoguchiet.al., Adv. Funct. Mater. 26 (2016) 302-3028. [Non-Patent Document 3] N. Nakashima et.al., Sic. Rep. 5 (2015) 7951 Summary of the Invention [Problem to be solved by the invention]
[0006] However, in the above-mentioned documents, the pn junction is a stacked or bridge type, which makes it difficult to make it thin, and there are also problems with physical strength and durability.
[0007] The present invention has been made in consideration of the above technical background, and aims to provide a thermoelectric conversion element, a thermoelectric conversion module, a wideband image sensor, and a method for manufacturing a thermoelectric conversion element that are easily thin-filmed and have excellent physical strength and durability. [Means for solving the problem]
[0008] The inventors have discovered that by making the surface area different between a semiconductor layer having a p-type semiconductor region and an n-type semiconductor region and containing a fibrous carbon nanostructure and a substrate on which this semiconductor layer is formed, a temperature gradient is generated from the center to the periphery of the semiconductor layer by irradiation with electromagnetic waves, and a thermoelectric effect is obtained.
[0009] A thermoelectric conversion element according to one embodiment of the present invention has the following configuration. (1) A thermoelectric conversion element according to a first aspect of the present invention comprises a substrate, a semiconductor layer having a p-type semiconductor region and an n-type semiconductor region formed on one main surface of the substrate, and an electrode layer electrically connected to the semiconductor layer, the substrate being made of a material having a smaller absorption rate for electromagnetic waves in any band having a wavelength in the range of 0.2 μm or more and 100 μm or less than that of the semiconductor layer, the substrate being formed so as to extend beyond the periphery of the semiconductor layer, the semiconductor layer including a fibrous carbon nanostructure, and a junction between the p-type semiconductor region and the n-type semiconductor region of the semiconductor layer being in contact with the one main surface of the substrate.
[0010] (2) A second aspect of the present invention is the thermoelectric conversion element of the first aspect, characterized in that the fibrous carbon nanostructure is made of a carbon nanotube.
[0011] (3) A third aspect of the present invention is characterized in that, in the thermoelectric conversion element of the second aspect, the carbon nanotubes have a diameter of 0.5 nm or more and 15 nm or less.
[0012] (4) A fourth aspect of the present invention is characterized in that, in the thermoelectric conversion element of any one of the first to third aspects, an i-type semiconductor region is further formed at the junction between the p-type semiconductor region and the n-type semiconductor region.
[0013] (5) A fifth aspect of the present invention is the thermoelectric conversion element according to any one of the first to fourth aspects, characterized in that the substrate is a flexible substrate.
[0014] (6) A sixth aspect of the present invention is the thermoelectric conversion element according to any one of the first to fifth aspects, characterized in that the substrate is made of a material that is transmissible to the electromagnetic waves.
[0015] (7) A seventh aspect of the present invention is the thermoelectric conversion element according to any one of the first to sixth aspects, characterized in that the substrate is made of a film containing at least one of polyimide, cycloolefin, and benzocyclobutene.
[0016] (8) Aspect 8 of the present invention is characterized in that, in the thermoelectric conversion element of any one of aspects 1 to 7, the n-type semiconductor region includes a reduction-calcined product of the fibrous carbon nanostructure and an ionic surfactant.
[0017] (9) A ninth aspect of the present invention is the thermoelectric conversion element of the eighth aspect, characterized in that the ionic surfactant is an anionic surfactant.
[0018] A thermoelectric conversion module according to one embodiment of the present invention has the following configuration. (10) A thermoelectric conversion module according to a tenth aspect of the present invention is characterized in that it includes a plurality of thermoelectric conversion elements according to any one of the first to ninth aspects.
[0019] The wideband image sensor according to one embodiment of the present invention has the following configuration. (11) A wideband image sensor according to an eleventh aspect of the present invention is characterized in that the thermoelectric conversion module according to the tenth aspect is used as an imaging element.
[0020] A method for manufacturing a thermoelectric conversion element according to one embodiment of the present invention proposes the following configuration. (12) A manufacturing method for a thermoelectric conversion module of aspect 12 of the present invention is a manufacturing method for a thermoelectric conversion element of any one of aspects 1 to 9, characterized in that it at least comprises a composition liquid preparation step of preparing an n-type fibrous carbon nanostructure composition liquid containing the fibrous carbon nanostructure, an ionic surfactant, an n-type semiconductor dopant, and a solvent, and a p-type fibrous carbon nanostructure composition liquid containing the fibrous carbon nanostructure and a solvent, a film formation step of spreading the n-type fibrous carbon nanostructure composition liquid and the p-type fibrous carbon nanostructure composition liquid on a transfer plate to form a film, a firing step of firing the film under a reducing atmosphere to obtain the semiconductor layer, and a transfer step of transferring the semiconductor layer from the transfer plate to the substrate. Effect of the Invention
[0021] According to the present invention, it is possible to provide a thermoelectric conversion element, a thermoelectric conversion module, a wideband image sensor, and a method for manufacturing a thermoelectric conversion element that can be easily made into a thin film and has excellent physical strength and durability. [Brief description of the drawings]
[0022] [Figure 1] 1 is a schematic structural diagram showing a thermoelectric conversion element according to one embodiment of the present invention. [Diagram 2] 1 is a flowchart showing a step-by-step method for manufacturing a thermoelectric conversion element according to one embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram showing a film forming process. [Figure 4] FIG. [Diagram 5] FIG. 1 is a schematic diagram showing a measurement device used in Verification Example 1. [Figure 6] 1 is a graph showing the results of Verification Example 1. [Figure 7] 1 is a graph showing the results of Verification Example 1. [Figure 8] FIG. 13 is a schematic diagram showing a measurement device used in Verification Example 2. [Figure 9] 13 is a graph showing the results of Verification Example 2. [Figure 10] 13 is a graph showing the results of Verification Example 2. [Figure 11] FIG. 1 is a schematic diagram showing a wideband image sensor according to an embodiment of the present invention. [Figure 12] FIG. 13 is a schematic diagram showing a measurement device used in Verification Example 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Hereinafter, the embodiments of the present invention will be described in detail with reference to the drawings. Note that the drawings used in the following description may show characteristic parts in an enlarged scale for the sake of convenience in order to make the characteristics easier to understand, and the dimensional ratios of each component may not necessarily be the same as in reality. In addition, the materials, dimensions, etc. exemplified in the following description are merely examples, and the present invention is not necessarily limited to them, and may be appropriately modified and implemented within a range that does not change the effects of the present invention.
[0024] (Thermoelectric conversion element) FIG. 1 is a schematic structural diagram showing a thermoelectric conversion element according to one embodiment of the present invention. A thermoelectric conversion element 10 of one embodiment of the present invention has a substrate 11, a semiconductor layer 14 having a p-type semiconductor region 12 and an n-type semiconductor region 13 formed on one main surface 11a of the substrate 11, and electrode layers 15a, 15b electrically connected to the p-type semiconductor region 12 and the n-type semiconductor region 13, respectively.
[0025] The substrate 11 of this embodiment is formed, for example, in a rectangular shape. When viewed from above in a plan view, the substrate 11 is formed to a size that extends beyond the periphery of the semiconductor layer 14, which will be described in detail later. That is, the surface area of one main surface 11a of the substrate 11 is made larger than the surface area of one surface 14a of the semiconductor layer 14.
[0026] Furthermore, substrate 11 is made of a material that has a lower absorptance than semiconductor layer 14 for electromagnetic waves in any band having a wavelength in the range of 0.2 μm or more and 100 μm or less, which is the wavelength range of electromagnetic waves irradiated to thermoelectric conversion element 10. For example, substrate 11 may be made of a material that has a lower absorptance than semiconductor layer 14 for electromagnetic waves in any wavelength range within the wavelength range of about 200 nm to 3000 nm, which is the wavelength range of electromagnetic waves radiated by sunlight.
[0027] The constituent material of the substrate 11 may be, for example, a dielectric sheet made of resin or the like. If the substrate 11 is made of a flexible substrate made of soft resin or the like, it can be made into a bendable thermoelectric conversion element 10. It is also preferable that the substrate 11 is made of a material that can transmit electromagnetic waves in the wavelength range irradiated to the thermoelectric conversion element 10. In this embodiment, a polyimide film, which is a bendable flexible substrate, is used as the substrate 11, but the present invention is not limited to this. For example, a film of cycloolefin or benzocyclobutene can also be used.
[0028] The semiconductor layer 14 of the present embodiment is formed, for example, in a rectangular shape as a whole. The semiconductor layer 14 is formed to be smaller than the substrate 11 when viewed in a plan view from above, and one main surface 11a of the substrate 11 is exposed outside the periphery of the semiconductor layer 14.
[0029] Moreover, the semiconductor layer 14 may be formed so that at least the junction (pn junction E) between the p-type semiconductor region 12 and the n-type semiconductor region 13 is in contact with one main surface 11a of the substrate 11. In this embodiment, the entire lower surface side of the semiconductor layer 14 including the p-type semiconductor region 12 and the n-type semiconductor region 13 is formed so as to be in contact with one main surface 11a of the substrate 11.
[0030] Such a semiconductor layer 14 is composed of a thin film containing a fibrous carbon nanostructure. More specifically, the p-type semiconductor region 12 constituting the semiconductor layer 14 of this embodiment is composed of a fibrous carbon nanostructure, and the n-type semiconductor region 13 is composed of a fibrous carbon nanostructure, an n-type semiconductor dopant, and a surfactant.
[0031] In this embodiment, the n-type semiconductor dopant constituting the n-type semiconductor region 13 is a reduction-calcined product of a fibrous carbon nanostructure and an ionic surfactant, and the cation of the ionic surfactant acts as an n-type semiconductor dopant. Furthermore, the fibrous carbon nanostructure exhibits the characteristics of a p-type semiconductor when no dopant is added.
[0032] The fibrous carbon nanostructure contained in the semiconductor layer 14 is not particularly limited as long as it is a nano-sized carbon structure having electrical conductivity, and carbon nanotubes (CNTs), carbon nanohorns, carbon nanofibers, etc. can be used. From the viewpoint of ensuring electrical conductivity while stabilizing the properties of the composite material as an n-type semiconductor, the fibrous carbon nanostructure is preferably a carbon nanotube (CNT).
[0033] The CNT, which is an example of a fibrous carbon nanostructure, may be a single-walled carbon nanotube or a multi-walled carbon nanotube, but it is preferable that the CNT contains at least a single-walled CNT. If the single-walled CNT is used as the CNT, the conductivity of the semiconductor layer 14 can be increased and the Seebeck coefficient can be sufficiently secured, and the characteristics as an n-type semiconductor in the n-type semiconductor region 13 can be stabilized.
[0034] The proportion of single-walled CNTs in the CNTs is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more. The proportion of single-walled CNTs in the CNTs can be determined by counting the number of single-walled CNTs among 100 CNTs randomly selected using a transmission electron microscope.
[0035] The average diameter of the fibrous carbon nanostructures may be 0.5 nm or more and 15 nm or less, preferably 1 nm or more and 10 nm or less, and more preferably 2.5 nm or more and 6 nm or less. If the average diameter of the fibrous carbon nanostructures is 0.5 nm or more, aggregation of the fibrous carbon nanostructures is suppressed, which contributes to stabilizing the characteristics as an n-type semiconductor in the n-type semiconductor region 13.
[0036] The average length of the fibrous carbon nanostructures is preferably 0.1 μm or more, preferably 1 cm or less, and more preferably 3 mm or less. By using fibrous carbon nanostructures whose average length is within the above range, the characteristics as an n-type semiconductor can be stabilized in the n-type semiconductor region 13. The average length of the fibrous carbon nanostructures can be determined by measuring the lengths of 100 randomly selected fibrous carbon nanostructures using a transmission electron microscope.
[0037] It is preferable that the relationship between the average diameter (Av) and the standard deviation (σ) of the diameter of the fibrous carbon nanostructure satisfies the following formula 1. 0.20<(3σ / Av)<0.80 (1) By satisfying the relationship of formula 1, the characteristics of the n-type semiconductor in the n-type semiconductor region 13 can be stabilized.
[0038] In addition, the "average diameter (Av) of fibrous carbon nanostructures" and the "standard deviation of the diameters of fibrous carbon nanostructures (σ: sample standard deviation)" in the above-mentioned formula (1) can each be determined by measuring the diameters (outer diameters) of 100 randomly selected fibrous carbon nanostructures using a transmission electron microscope.
[0039] The BET specific surface area of the fibrous carbon nanostructure is 600m 2 / g or more, and 2 / g or more. 2 The use of a fibrous carbon nanostructure having a BET specific surface area of 100 / g or more can stabilize the characteristics as an n-type semiconductor in the n-type semiconductor region 13. The upper limit of the BET specific surface area of the fibrous carbon nanostructure is not particularly limited, but may be, for example, 2600 m 2 / g or less.
[0040] The fibrous carbon nanostructure preferably has a ratio of G band peak intensity to D band peak intensity (G / D ratio) in the Raman spectrum of 5 or less. Here, the G / D ratio is an index generally used to evaluate the quality of fibrous carbon nanostructures such as CNTs. The Raman spectrum of a carbon nanostructure assembly measured by a Raman spectrometer contains a G band (1600 cm -1 around 1350cm -1 The G band is a vibration mode originating from the hexagonal lattice structure of graphite, which is the cylindrical surface of the fibrous carbon nanostructure, and the D band is a vibration mode originating from the amorphous part.
[0041] Therefore, the higher the peak intensity ratio of the G band to the D band (G / D ratio), the more crystalline the fibrous carbon nanostructure can be evaluated as. If the G / D ratio is 5 or less, there will be many defect structures on the surface of the fibrous carbon nanostructure, and the ionic surfactant will be more likely to wet the surface of the fibrous carbon nanostructure. Therefore, it is presumed that the ionic surfactant can more uniformly coat the surface of the fibrous carbon nanostructure, and the oxidation of the fibrous carbon nanostructure can be more effectively prevented.
[0042] The fibrous carbon nanostructure constituting the semiconductor layer 14 as described above can be manufactured by, for example, a method based on catalytic hydrogen reduction of carbon dioxide, an arc discharge method, a chemical vapor deposition method (CVD method), a laser evaporation method, a vapor phase growth method, a vapor phase flow method, a HiPCO method, etc. In addition, as the fibrous carbon nanostructure, for example, one obtained by the eDIPS method, which is a type of vapor phase flow method, can also be used (hereinafter, carbon nanotubes obtained by the eDIPS method may be referred to as "eDIPS-CNT").
[0043] As the fibrous carbon nanostructure, it is preferable to use one obtained by a method (super-growth method; see International Publication No. 2006 / 011655) in which, when a raw material compound and a carrier gas are supplied onto a substrate having a catalyst layer for producing carbon nanotubes on its surface and CNTs are synthesized by a CVD method, a trace amount of an oxidizing agent (catalyst activation material) is made present in the system to dramatically improve the catalytic activity of the catalyst layer (hereinafter, carbon nanotubes obtained by the super-growth method may be referred to as "SGCNT"). This is because SGCNTs can stably maintain the composite material as n-type compared to other CNTs.
[0044] The reason why SGCNTs are able to stably maintain the n-type composite material compared to other CNTs is not entirely clear, but it is presumed to be as follows. That is, CNTs such as eDIPS-CNTs generally have high crystallinity and few defect structures on the surface. For example, the G / D ratio of eDIPS-CNTs is usually 30 or more.
[0045] In contrast, SGCNTs usually have a G / D ratio of 5 or less, and structural defects such as 5-membered or 7-membered rings other than 6-membered rings often occur during the CNT manufacturing process. As described above, structural defects improve the wettability of the ionic surfactant, and the SGCNTs are more uniformly covered with the ionic surfactant. For this reason, it is presumed that in the n-type semiconductor region 13, the SGCNTs are more effectively prevented from being oxidized (to p-type), allowing them to be maintained as n-type.
[0046] The fibrous carbon nanostructure may have a functional group such as a carboxyl group introduced therein. The introduction of the functional group can be carried out by a known method such as an oxidation treatment method using hydrogen peroxide or nitric acid, or a contact treatment method with a supercritical fluid, a subcritical fluid, or a high-temperature and high-pressure fluid.
[0047] The n-type semiconductor region 13 constituting the semiconductor layer 14 reverts to a p-type semiconductor through an oxidation reaction. In this embodiment, however, the n-type semiconductor region 13 contains a reduction-calcined product of a fibrous carbon nanostructure and an ionic surfactant, thereby stably maintaining the n-type semiconductor characteristics for a long period of time.
[0048] The reason why the n-type semiconductor region 13 constituting the semiconductor layer 14 of this embodiment can maintain n-type semiconductor characteristics for a long period of time is not entirely clear, but it is presumed to be as follows. That is, when a reduced fibrous carbon nanostructure is adsorbed (doped) with cations derived from, for example, an ionic surfactant, the fibrous carbon nanostructure exhibits n-type semiconductor characteristics. At this time, if the cations adsorbed to the fibrous carbon nanostructure are small ions such as alkali metal ions or alkaline earth metal ions, they will be detached from the fibrous carbon nanostructure in the air.
[0049] In addition, since the surface of the fibrous carbon nanostructure is exposed to the outside, it is oxidized by oxygen in the air, and the fibrous carbon nanostructure reverts to a p-type semiconductor and is unable to maintain its n-type semiconductor properties, but in the reduction-calcined product of an ionic surfactant and a fibrous carbon nanostructure, cations derived from the ionic surfactant are adsorbed onto the fibrous carbon nanostructure, and the main body of the ionic surfactant protects the fibrous carbon nanostructure from oxidation by oxygen in the air, which is why it can be inferred that the fibrous carbon nanostructure can maintain its n-type semiconductor properties for a long period of time.
[0050] The ionic surfactant contained in the n-type semiconductor region 13 constituting the semiconductor layer 14 is not particularly limited as long as it generates cations as n-type dopants that are adsorbed to the fibrous carbon nanostructure when dissolved in a solvent such as water, and for example, a known ionic surfactant can be used.
[0051] As the ionic surfactant, it is preferable to use an anionic surfactant or a cationic surfactant, but an amphoteric surfactant may also be used. It is believed that the surfactant can spread on the surface of the fibrous carbon nanostructure together with the solvent by lowering the surface tension (surface free energy) of the solvent in which it is contained.
[0052] In addition, it is preferable that the ionic surfactant has a ring structure. Specifically, in the ionic surfactant, the anion molecule or cationic molecule that becomes a surface active ion when dissolved in a solvent such as water preferably has a ring structure. The ring structure has a strong interaction with the six-membered carbon ring of a fibrous carbon nanostructure such as CNT. Therefore, if the ionic surfactant has a ring structure, the surface active ion can be more firmly adsorbed to the fibrous carbon nanostructure, and the n-type of the obtained composite material can be stabilized.
[0053] The ring structure of the ionic surfactant is not particularly limited as long as it exhibits an interaction with the six-membered carbon ring of the fibrous carbon nanostructure, and may be either a monocyclic structure or a polycyclic structure. Examples of the monocyclic structure include aromatic hydrocarbon rings such as benzene ring; aliphatic hydrocarbon rings such as cyclopentane ring, cyclohexane ring, cycloheptane ring, cyclooctane ring, cyclononane ring, cyclodecane ring, cycloundecane ring, and cyclododecane ring; aromatic heterocycles such as pyrrole ring, furan ring, thiophene ring, pyran ring, pyridine ring, pyridazine ring, pyrimidine ring, pyrazine ring, triazine ring, pyrazole ring, isoxazole ring, isothiazole ring, imidazole ring, oxazole ring, thiazole ring, triazole ring, oxadiazole ring, and thiadiazole ring; aliphatic heterocycles such as pyrrolidine ring, tetrahydrofuran ring, tetrahydrothiophene ring, piperidine ring, tetrahydropyran ring, tetrahydrothiopyran ring, piperazine ring, morpholine ring, and dioxane ring. Here, the heterocycle refers to a ring structure having one or more heteroatoms other than carbon, and may be a saturated ring or an unsaturated ring. Additionally, heteroatoms include, but are not limited to, nitrogen atoms, oxygen atoms, and sulfur atoms.
[0054] The polycyclic structure may be a polycyclic structure in which two or more monocyclic rings are condensed, a polycyclic structure in which two or more rings are bonded to each other via a single bond or a linking group, a polycyclocyclic structure having two or more rings, or a spirocyclic structure. The polycyclic structure may be composed of two or more aromatic monocyclic rings, two or more aliphatic monocyclic rings, or one or more aromatic monocyclic rings and one or more aliphatic monocyclic rings.
[0055] Specific examples of the polycyclic structure include a naphthalene ring, a biphenyl ring, an anthracene ring, and a phenyl ring. aromatic hydrocarbon rings such as a nanthrene ring; aliphatic hydrocarbon rings such as a decalin ring, a hydrindane ring, an adamantane ring, a norbornane ring, a norbornene ring, an isobornane ring, a tricyclodecane ring, a tetracyclododecane ring, and a sterol ring; rings composed of an aliphatic hydrocarbon ring and an aromatic hydrocarbon ring such as a tetralin ring, an indane ring, a cyclopentylbenzene ring, and a cyclohexylbenzene ring; aromatic heterocycles such as an indole ring, an indazole ring, a benzimidazole ring, a benzoxazole ring, a benzothiazole ring, a quinoline ring, an isoquinoline ring, a cinnoline ring, a phthalazine ring, a quinazoline ring, a quinoxaline ring, a naphthyridine ring, a pteridine ring, a carbazole ring, and an acridine ring; aliphatic heterocycles such as a 7-oxanorbornane ring, a 7-thionorbornane ring, and a 7-azanorbornane ring; and polycyclic structures composed of an aliphatic heterocycle and an aromatic hydrocarbon ring such as an indoline ring and a chroman ring. From the viewpoint of further stabilizing the n-type of the composite material, the ring structure preferably contains an aromatic hydrocarbon ring.
[0056] Furthermore, the ring structure of the ionic surfactant may have a substituent, which includes, but is not limited to, a halogen atom (such as a fluorine atom, a chlorine atom, a bromine atom, or an iodine atom), a hydroxyl group, an alkyl group having 1 to 6 carbon atoms, an alkenyl group having 2 to 6 carbon atoms, an amino group, a carbamoyl group, a nitro group, and a cyano group.
[0057] An anionic surfactant is a surfactant that separates into a cation as a counter ion and an anion as a surface active ion when dissolved in a solvent such as water. The anionic surfactant is not particularly limited, and a conventionally known anionic surfactant can be used. For example, a carboxylate type, a sulfate ester salt type, a sulfonate type, and a phosphate ester salt type anionic surfactant can be used as the anionic surfactant.
[0058] Examples of counter ions of the anionic surfactant include ammonium ions, primary to quaternary ammonium cations, alkali metal ions, and alkaline earth metal ions. Among them, from the viewpoint of good adsorption to fibrous carbon nanostructures such as CNTs, alkali metal ions such as sodium ions and alkaline earth metal ions such as potassium ions are preferred.
[0059] The carboxylic acid type anionic surfactant is not particularly limited, but may be, for example, a compound represented by the formula R-COO - X + (R represents a hydrocarbon group having 8 or more carbon atoms which may have a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom; X + represents a counter ion). R may have the ring structure described above. R may also have a substituent of the ring structure described above.
[0060] Specific examples of carboxylate-type anionic surfactants include alkyl (C8-C16) carboxylates such as sodium octanoate, sodium decanoate, sodium laurate, sodium myristate, and sodium stearate; halogenated alkyl (C8-C16) carboxylates such as sodium perfluorooctanoate and sodium perfluorononanoate; sodium N-lauroyl sarcosine, sodium cocoyl glutamate, α-sulfofatty acid methyl ester salts, sodium cholate (SC), sodium deoxycholate, and sodium glycocholate.
[0061] The sulfate salt type anionic surfactant is, but is not limited to, for example, a surfactant represented by the formula R-OSO 3 - X + (R represents a hydrocarbon group having 8 or more carbon atoms which may have a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom; X + represents a counter ion), or an alcohol sulfate represented by the formula RO(CH 2 CH 2 O) n SO 3 - X + (R,X + is as described above, and n is an integer of 1 or more).
[0062] Specific examples of sulfate salt-type anionic surfactants include alkyl (C8-C16) sulfate salts such as sodium dodecyl sulfate (SDS), ammonium dodecyl sulfate, and sodium myristyl sulfate; alkyl (C8-C16) ether sulfate salts such as sodium laureth sulfate; and polyoxyethylene alkyl (C8-C16) aryl sulfonates such as sodium polyoxyethylene alkyl (C8-C16) phenol sulfonate.
[0063] The sulfonate type anionic surfactant is, but is not limited to, for example, a compound represented by the formula R-SO 3 - X + (R represents a hydrocarbon group having 8 or more carbon atoms which may have a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom; X + represents a counter ion), or a sulfonate represented by the formula R-CH 2 =CHCH 2 SO 3 - X + (R,X + is as described above).
[0064] Specific examples of sulfonate-type anionic surfactants include alkyl (C8-C16) sulfonates such as sodium octanesulfonate, sodium decane sulfonate, and sodium lauryl sulfonate; linear alkyl (C8-C16) aryl sulfonates such as sodium octylbenzenesulfonate and sodium dodecylbenzenesulfonate (SDBS); alkylaryl sulfonates such as sodium toluenesulfonate, sodium cumenesulfonate, and sodium butylnaphthalenesulfonate; halogenated alkyl sulfonates such as perfluorooctanesulfonate; and α-olefin (C8-C16) sulfonates such as sodium 1-tetradecenesulfonate and sodium hexadecenesulfonate.
[0065] The phosphate ester salt type anionic surfactant is, but is not limited to, for example, a surfactant represented by the formula R-OPO 3 - X + (R represents a hydrocarbon group having 8 or more carbon atoms which may have a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom; X + represents a counter ion). Specific examples of phosphate ester salt-type anionic surfactants include alkyl (C8-C16) phosphate ester salts such as sodium lauryl phosphate.
[0066] A cationic surfactant is a surfactant that separates into an anion as a counter ion and a cation as a surface active ion when dissolved in a solvent such as water. The cationic surfactant is not particularly limited, and any conventionally known cationic surfactant can be used.
[0067] As the cationic surfactant, for example, quaternary ammonium salt type, amine salt type, and pyridinium salt type cationic surfactants can be used. The counter ion of the cationic surfactant is not particularly limited, and is, for example, an ion of a halogen atom such as bromine, iodine, or chlorine.
[0068] The quaternary ammonium salt type cationic surfactant is, but is not limited to, for example, a compound represented by the formula R 1 R 2 R 3 R 4 N + X + (R 1 R 2 R 3 R 4 each independently represents a hydrocarbon group which may have a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom (provided that R 1 R 2 R 3 R 4 At least one of X has 8 or more carbon atoms. - represents a counter ion.) It is a quaternary ammonium salt represented by the formula: 1 R 2 R 3 R 4 may each independently have the ring structure described above. 1 R 2 R 3 R 4 may each independently have a substituent of the ring structure described above.
[0069] Specific examples of quaternary ammonium salt type cationic surfactants include tetraalkylammonium salts such as octyltrimethylammonium chloride, dodecyltrimethylammonium chloride, cetyltrimethylammonium chloride, stearyltrimethylammonium chloride, cetyltrimethylammonium bromide (CTAB), dimethyldioctadecylammonium chloride (DODMAC), didecyldimethylammonium chloride, and distearyldimethylammonium chloride; benzyltrimethylammonium chloride, benzyltriethylammonium chloride, and the like. Examples of aryl ammonium salts include trialkylmonoarylammonium salts such as triethylbenzylammonium chloride, triethylbenzylammonium chloride, benzyldimethyltetradecylammonium chloride, benzalkonium chloride, and benzalkonium bromide; dialkyldiarylammonium salts; and tetraarylammonium salts.
[0070] The amine salt type cationic surfactant is, but is not limited to, for example, a compound represented by the formula R 1 -NH 2 -HA (in the formula, R 1 represents a hydrocarbon group having 8 or more carbon atoms which may have a heteroatom such as a nitrogen atom, an oxygen atom or a sulfur atom, and A represents an acid such as hydrochloric acid; 1 R 2 -NH-HA (wherein, R 1 R 2 each independently represents a hydrocarbon group which may have a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom (provided that R 1 R 2 wherein at least one of the carbon atoms has 8 or more, and A represents an acid such as hydrochloric acid; and 1 R 2 R 3 -N-HA(wherein, R 1 R 2 R 3 each independently represents a hydrocarbon group which may have a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom (provided that R 1 R 2 R 3 At least one of the carbon atoms is 8 or more, and A represents an acid such as hydrochloric acid. 1 R 2 R 3 may each independently have the ring structure described above. 1 R 2 R 3 may each independently have a substituent of the ring structure described above.
[0071] Specific examples of the amine salt type cationic surfactant include monoalkylamine hydrochlorides such as dodecylamine hydrochloride; dialkylamine hydrochlorides such as didodecylamine hydrochloride; and trialkylamine hydrochlorides such as tridodecylamine hydrochloride.
[0072] The pyridinium salt type cationic surfactant is, but is not limited to, for example, a compound represented by the formula RC 5 H 5 N+ X - (R represents a hydrocarbon group having 8 or more carbon atoms which may have a heteroatom such as a nitrogen atom, an oxygen atom, or a sulfur atom; X + represents a counter ion). Specific examples of pyridinium salt-type cationic surfactants include alkyl (C8-C16) pyridinium salts such as dodecylpyridinium chloride and cetylpyridinium chloride (CPC).
[0073] In this embodiment, the p-type semiconductor region 12 is composed of a fibrous carbon nanostructure that exhibits p-type semiconductor characteristics in the absence of a p-type dopant. In addition, other materials that can be used as the constituent materials of the p-type semiconductor region 12 include, for example, bismuth tellurium-based compounds, antimony-based compounds, silicon-based compounds, metal oxide-based compounds, Heusler alloy-based compounds, conductive polymer compounds such as polythiophene-based compounds, polyacetylene-based compounds, polyaniline-based compounds, and polypyrrole-based compounds, as well as composite materials of these compounds.
[0074] The electrode layers 15a and 15b are composed of conductive films electrically connected to the p-type semiconductor region 12 and the n-type semiconductor region 13, respectively. The constituent material of the electrode layers 15a and 15b is not particularly limited as long as it is conductive, such as a metal, an alloy, or a semiconductor, but it is preferable to form the electrode layers 15a and 15b from a metal or alloy with high conductivity, such as gold, silver, copper, aluminum, platinum, or an alloy of these.
[0075] If the electrode layers 15a, 15b are formed at the ends of the p-type semiconductor region 12 and the n-type semiconductor region 13, respectively, with the same thickness as the semiconductor layer 14, as in this embodiment, the thermoelectric conversion element 10 can be easily made thin.
[0076] The operation of the thermoelectric conversion element 10 of this embodiment having the above-mentioned configuration will be described. When electromagnetic waves, such as sunlight, are incident on the side of the thermoelectric conversion element 10 of this embodiment on which the semiconductor layer 14 is formed, the substrate 11 and the semiconductor layer 14 are heated by infrared rays (heat rays) contained in the sunlight.
[0077] Substrate 11 on which semiconductor layer 14 is provided is made of a material that has a lower absorption rate of sunlight (electromagnetic waves) than semiconductor layer 14, so when sunlight is uniformly irradiated onto thermoelectric conversion element 10, semiconductor layer 14 absorbs more sunlight than substrate 11. Furthermore, substrate 11 is formed so as to extend beyond the periphery of semiconductor layer 14, so a heat flow is generated from the center of semiconductor layer 14 toward the periphery, creating a temperature gradient.
[0078] The temperature gradient generated in the semiconductor layer 14 causes the semiconductor layer 14 to perform thermoelectric conversion, generating a potential difference between the p-type semiconductor region 12 and the n-type semiconductor region 13. This potential difference allows a generated current to be extracted between the electrode layers 15a and 15b. By this action, if the thermoelectric conversion element 10 of this embodiment is irradiated with, for example, sunlight as an electromagnetic wave, it can generate electricity as a solar power generation element.
[0079] Furthermore, since the thermoelectric conversion element 10 of this embodiment is configured by bonding a thin-film semiconductor layer 14 having a p-type semiconductor region 12 and an n-type semiconductor region 13 along one main surface 11a of a thin-film substrate 11, the thickness can be significantly reduced compared to a conventional thermoelectric conversion element having a three-dimensional structure in which a semiconductor layer is placed at a right angle to a substrate to generate a temperature gradient, and the element can be easily installed even in a small installation space.
[0080] Furthermore, in the thermoelectric conversion element 10 of this embodiment, the p-n junction, where the p-type semiconductor region 12 and the n-type semiconductor region 13 are joined, is configured to be in contact with one main surface 11a of the substrate 11. Therefore, compared to a conventionally known thermoelectric conversion element having a so-called bridge structure in which a p-n junction is formed by overlapping a part of a p-type semiconductor section and a part of an n-type semiconductor section in the thickness direction, a high-strength thermoelectric conversion element having no parts protruding in the thickness direction and high durability against external stress can be realized.
[0081] Furthermore, if the substrate 11 is made of a flexible substrate such as a polyimide film, as in the thermoelectric conversion element 10 of this embodiment, the semiconductor layer 14 containing the fibrous carbon nanostructures is also flexible enough to be bent, making it possible to install the thermoelectric conversion element 10 in a form such as by adhering it along a curved surface, for example.
[0082] The thermoelectric conversion element 10 of this embodiment, which has the above-mentioned characteristics, can act as a temperature sensor that does not require a power supply for sensing, and can transmit temperature information using electromotive force due to a temperature gradient. As a specific application example of such a thermoelectric conversion element 10, the thermoelectric conversion element 10 of this embodiment can be installed inside an automobile tire to detect a temperature rise inside the tire, thereby making it possible to detect signs of a tire burst due to volume expansion accompanying a temperature rise.
[0083] In addition, by attaching the thermoelectric conversion element 10 of this embodiment to the curved outer surface of a pipe that transports liquid or gas, it becomes possible to easily detect the pipe temperature as a temperature sensor that does not require a power supply for sensing. In addition, by installing the thermoelectric conversion element 10 of this embodiment in an outdoor environment where it is difficult to supply power for sensing, such as near a volcano that is under constant monitoring, it can be used as a temperature sensor for detecting signs of an eruption.
[0084] In the above-described embodiment, the pn junction is formed by providing the p-type semiconductor region 12 and the n-type semiconductor region 13 adjacent to each other as the semiconductor layer 14, but it is also possible to provide an i-type semiconductor (intrinsic semiconductor) region between the p-type semiconductor region and the n-type semiconductor region to form a pin junction. Such a pin junction may also be formed so as to be in contact with one main surface side of the substrate.
[0085] (Thermoelectric conversion module: wideband image sensor) A thermoelectric conversion module according to an embodiment of the present invention includes a plurality of thermoelectric conversion elements according to the above-described embodiment. More specifically, the thermoelectric conversion module is configured by arranging the semiconductor layers 14 of a plurality of thermoelectric conversion elements 10 in a planar manner in the X and Y directions on one surface of an arbitrary substrate. Such a thermoelectric conversion module can be used as a wideband image sensor capable of detecting the temperature distribution of an object to be detected.
[0086] FIG. 11 is a schematic diagram showing the wideband image sensor of this embodiment. The wideband image sensor 20 of this embodiment is configured, for example, by arranging a plurality of thermoelectric conversion elements 10 in the X and Y directions on one main surface of a substrate 21. Since each thermoelectric conversion element 10 is capable of detecting a wide band of electromagnetic waves from ultraviolet light to terahertz waves, it is possible to realize an ultra-wideband image sensor 20 that is not limited to heat detection but has a wavelength range of about 0.2 μm to 100 μm.
[0087] The substrate 21 is made of a material that has a smaller electromagnetic wave absorption rate than the semiconductor region in the wavelength band to be detected. In Fig. 11, the thermoelectric conversion element 10 corresponding to each pixel is formed so that the semiconductor region is smaller than the region 10 as shown in Fig. 1.
[0088] (Method of manufacturing thermoelectric conversion element) Next, a method for manufacturing the above-mentioned thermoelectric conversion element according to one embodiment of the present invention will be described. FIG. 2 is a flow chart showing a step-by-step method for producing a thermoelectric conversion element according to one embodiment of the present invention.
[0089] When manufacturing the thermoelectric conversion element of the embodiment shown in Figure 1, first, an n-type fibrous carbon nanostructure composition liquid (hereinafter referred to as n-type composition liquid) and a p-type fibrous carbon nanostructure composition liquid (hereinafter referred to as p-type composition liquid) are prepared (composition liquid preparation process S1).
[0090] The n-type liquid composition contains a fibrous carbon nanostructure, an ionic surfactant, an n-type semiconductor dopant, and a solvent. In this embodiment, the cation of the ionic surfactant acts as the n-type semiconductor dopant, so the ionic surfactant contains the n-type semiconductor dopant.
[0091] The p-type liquid composition contains a fibrous carbon nanostructure and a solvent. The fibrous carbon nanostructure acts as a p-type semiconductor, particularly in the absence of an n-type dopant.
[0092] The fibrous carbon nanostructures contained in the n-type composition liquid and the p-type composition liquid, and the ionic surfactant contained in the n-type composition liquid can be those listed in the embodiments of the thermoelectric conversion element described above.
[0093] In an n-type liquid composition, the ratio of ionic surfactant to the dispersion liquid composition in which fibrous carbon nanostructures are dispersed in a solvent may be 10 parts by mass or more of ionic surfactant per 100 parts by mass of the dispersion liquid composition, and preferably is 1,000 parts by mass or less of ionic surfactant per 100 parts by mass of the dispersion liquid composition.
[0094] The solvent contained in the n-type composition liquid and the p-type composition liquid is not particularly limited, and either water or an organic solvent can be used. The solvent may be used alone or in combination of two or more.
[0095] Specific examples of organic solvents include alcohols such as methanol, ethanol, and ethylene glycol; aromatic solvents such as toluene, xylene, ethylbenzene, anisole, trimethylbenzene, p-fluorophenol, p-chlorophenol, o-chlorophenol, and purple phenol; and ethers such as tetrahydrofuran, dioxane, cyclopentyl monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, propylene glycol monomethyl ether acetate, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, and 3-methoxybutyl acetate. ketones such as acetone, cyclohexanone, methyl isobutyl ketone, methyl ethyl ketone, and diisobutyl ketone; nitrogen-containing polar organic solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, 2-pyrrolidone, N-methyl-2-pyrrolidone, 1,3-dimethyl-2-imidazolidinone, N,N,N,N-tetramethylurea, N-methyl-ε-caprolactam, and hexamethylphosphoric triamide; esters such as ethyl acetate, methyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, n-pentyl acetate, methyl lactate, ethyl lactate, n-butyl lactate, γ-butyrolactone, and γ-valerolactone; and dimethyl sulfoxide.
[0096] In this embodiment, water is used as the solvent from the viewpoint of improving the dispersibility of the fibrous carbon nanostructures.
[0097] The n-type composition liquid and the p-type composition liquid can be prepared by subjecting the mixture of the respective constituent materials described above to any dispersion treatment. For example, the dispersion treatment described in International Publication No. 2016 / 103706 that produces a cavitation effect or a disintegration effect can be used as the dispersion treatment.
[0098] Next, the obtained n-type composition liquid and p-type composition liquid are each spread on a transfer plate to form a film (film forming step S2). In this embodiment, as shown in Fig. 3, for example, a circular membrane filter is used as a transfer plate, and this membrane filter is placed on a suction device, and then an n-type composition liquid and a p-type composition liquid are dropped and sucked, respectively, to obtain a film formed in one semicircular region of the membrane filter of the n-type composition liquid and in the other region of the p-type composition liquid. Note that after the formation of the film, a drying process for drying the film may be further provided.
[0099] This method of forming a film by dropping n-type and p-type composition liquids is called the drop casting method, which has easy scalability, high deposition rate, and does not require a vacuum environment, making it more cost-effective and simpler than other film formation methods.
[0100] Next, the film obtained in the film-forming step S2 is fired in a reducing atmosphere to obtain a semiconductor layer (firing step S3). The firing step S3 is a step of firing the film obtained in the above-mentioned film formation step S2 in a reducing atmosphere at a temperature lower than the decomposition temperature of the fibrous carbon nanostructure and the ionic surfactant. By firing the film in a reducing atmosphere, the thin film portion of the n-type composition liquid can well protect the surface of the fibrous carbon nanostructure by the residue of the ionic surfactant. This allows the obtained semiconductor layer to stably maintain the characteristics as an n-type semiconductor.
[0101] Here, the method of firing the film-formed body in a reducing atmosphere is not particularly limited, and for example, the film-formed body may be placed in a conventionally known heating device such as an oven, and the inside of the heating device may be made into a reducing atmosphere to heat the coating. The reducing atmosphere may be formed, for example, by refluxing a reducing gas in the heating device. The reducing gas to be supplied is not particularly limited as long as it can reduce the fibrous carbon nanostructures, and for example, hydrogen gas (H 2 ), carbon monoxide gas (CO), hydrocarbon gas (CH 4 , C 3 H8 , C 4 H 10 etc.), with hydrogen gas being particularly preferred.
[0102] In addition, it is also preferable that the reducing atmosphere further contains an arbitrary inert gas such as argon gas. The concentration of the reducing gas is not particularly limited as long as it can reduce the fibrous carbon nanostructure, but is generally more than 0 volume %, preferably 4 volume % or more, and generally 10 volume % or less, preferably 6 volume % or less, based on the total atmospheric gas in the heating device.
[0103] If the concentration of the reducing gas is 4% by volume or more and 6% by volume or less with respect to the entire atmosphere gas, the semiconductor type of the n-type semiconductor region to be generated can be stably maintained as n-type, and if it is 5% by volume, the semiconductor type can be more stably maintained as n-type. In this embodiment, the atmosphere gas in the heating device contains 95% by volume of argon gas and 5% by volume of hydrogen gas.
[0104] The calcination time in the calcination step S3 is not particularly limited as long as the fibrous carbon nanostructure is sufficiently reduced and the surface of the fibrous carbon nanostructure can be sufficiently protected by the ionic surfactant, but is generally more than 30 minutes and less than 3 hours.
[0105] The firing temperature in the firing step S3 may be a temperature below the decomposition temperature of the fibrous carbon nanostructure and the ionic surfactant. If the firing temperature is equal to or higher than the decomposition temperature, the fibrous carbon nanostructure and the ionic surfactant will decompose. The specific decomposition temperature is about 550°C when SGCNTs are used as the fibrous carbon nanostructure.
[0106] The lower limit of the baking temperature is not particularly limited as long as the residue of the ionic surfactant can protect the surface of the fibrous carbon nanostructure, but from the viewpoint of more uniform protection of the surface of the fibrous carbon nanostructure, it is preferable that the temperature be equal to or higher than the melting point of the ionic surfactant.
[0107] Next, the semiconductor layer obtained in the firing step S3 is transferred onto a substrate to obtain a thermoelectric conversion element (transfer step S4). In this embodiment, as shown in Fig. 4, a part of the semiconductor layer formed in, for example, a circular shape obtained in the firing step S3 is cut into a rectangle, and the cut rectangular semiconductor layer is transferred from the transfer plate to a substrate and bonded. When cutting out, the junction (pn junction) between the p-type semiconductor region and the n-type semiconductor region may be positioned in the center of the cut out region. In addition, the cut out size of the semiconductor layer is made smaller than the size of the substrate.
[0108] The substrate to which the transfer is to be made may be any of the substrates described in the above embodiment of the thermoelectric conversion element, and may be, for example, a glass substrate or a plastic substrate made of a heat-resistant resin such as polyimide. The size of the substrate is larger than the size of the semiconductor layer cut into a rectangle.
[0109] Next, electrode layers are formed on the ends of the p-type semiconductor region and the n-type semiconductor region that constitute the semiconductor layer (electrode layer formation step S5). The electrode layers may be formed using the materials constituting the electrode layers described in the above-mentioned embodiment of the thermoelectric conversion element. The electrode layers may be formed by electroless plating, bonding of a metal thin film, or the like.
[0110] By the above steps, a thermoelectric conversion element of this embodiment can be obtained, in which a semiconductor layer having an n-type semiconductor region and a p-type semiconductor region, which includes a reduction-calcined product of a fibrous carbon nanostructure and an ionic surfactant, is bonded to a substrate and an electrode layer is formed.
[0111] Although the embodiments of the present invention have been described above, these embodiments are presented as examples and are not intended to limit the scope of the invention. These embodiments can be implemented in various other forms, and various omissions, substitutions, and modifications can be made without departing from the spirit of the invention. These embodiments and their modifications are included in the scope of the invention and its equivalents described in the claims, as well as in the scope and spirit of the invention. EXAMPLES
[0112] The present invention will be specifically described below based on examples, but the present invention is not limited to these examples. (Verification example 1) In the verification example 1, the measurement device shown in FIG. 5 was used. (1) The thermoelectric conversion element of the above-described embodiment was placed on a stage made of glass wool. (2) An artificial solar lamp (SOLAX100W type: manufactured by Ceric Co., Ltd.) was installed on top of the thermoelectric conversion element as a light source (heat source). (3) An aluminum film was bonded to one side of the glass wool and a polyimide sheet was bonded to the other side. An irradiation control plate with an opening in the center was placed below the light source, and the electromagnetic waves irradiated from the light source were controlled so that they would only hit the thermoelectric conversion element.
[0113] Electromagnetic waves (sunlight) were irradiated from an artificial sunlamp onto the thermoelectric conversion element of the measuring device shown in Figure 5, and the voltage value between the electrode layers formed on the ends of the p-type semiconductor region and the n-type semiconductor region was measured. The measurement was carried out for 75 minutes from the start of irradiation. The results are shown in Figure 6.
[0114] According to the results shown in FIG. 6, it was confirmed that the thermoelectric conversion element of this embodiment can stably generate electricity (thermoelectric conversion) within a slight voltage fluctuation range of about 0.5 mV by irradiating sunlight.
[0115] In addition, the voltage was measured while changing the distance between the electrode layers to 10 mm, 20 mm, 30 mm, and 40 mm with a constant light intensity. The results are shown in Figure 7.
[0116] According to the results shown in Fig. 7, it was confirmed that the electromotive force of the thermoelectric conversion element of this embodiment increases as the distance between the electrode layers increases. In particular, when the distance between the electrode layers exceeds 20 mm, the electromotive force increases rapidly. This is believed to be because the surface areas of the p-type semiconductor region and the n-type semiconductor region into which sunlight is incident increase as the distance between the electrode layers increases.
[0117] (Verification example 2) In Verification Example 2, a measurement device shown in FIG. 8 was used. (1) The thermoelectric conversion element of the above-mentioned embodiment was used in a single layer, a double layer, and a triple layer configuration. The substrate of each thermoelectric conversion element was a polyimide sheet that was heat-permeable. (2) Heaters equipped with heat flux sensors were placed on the substrate side and the semiconductor layer side of the thermoelectric conversion element, respectively, so that heat (electromagnetic waves) could be irradiated from both sides of the thermoelectric conversion element.
[0118] The relationship between temperature and output voltage value (mV), measured using the measuring device shown in Fig. 8, is shown in a graph in Fig. 9. The relationship between temperature and output power value (nW) is shown in a graph in Fig. 10. According to the results shown in FIG. 9 and FIG. 10, it was confirmed that the more the number of layers of the thermoelectric conversion elements is increased and the higher the temperature is, the higher the voltage value and output power value that can be obtained.
[0119] (Verification example 3) In verification example 3, the irradiation control plate was removed from the measurement device of verification example 1, and electromagnetic waves (sunlight) were irradiated from an artificial sunlamp toward the thermoelectric conversion element placed on a stage made of glass wool and its surrounding area, and the voltage value between the electrode layers formed on the ends of the p-type semiconductor region and the n-type semiconductor region was measured, as in the measurement device shown in Fig. 12. In verification example 3, it was confirmed that stable power generation (thermoelectric conversion) was possible within a slight voltage fluctuation range of about 0.5 mV. [Industrial Applicability]
[0120] According to the present invention, a thermoelectric conversion element capable of generating electricity by thermoelectric conversion of electromagnetic waves is obtained using a fibrous carbon nanostructure. The use of such a thermoelectric conversion element does not require an external power supply for operation, and can be used as a thermal sensor that is easily thinned and can be applied to temperature management of various devices. Therefore, the thermoelectric conversion element, thermoelectric conversion module, and manufacturing method of the thermoelectric conversion element of the present invention have industrial applicability. [Explanation of symbols]
[0121] 10...Thermoelectric conversion element 11...Substrate 12...p-type semiconductor region 13...n-type semiconductor region 14...Semiconductor layer 15a, 15b...electrode layer
Claims
1. a substrate; a semiconductor layer having a p-type semiconductor region and an n-type semiconductor region formed on one main surface of the substrate; and an electrode layer electrically connected to the semiconductor layer; the substrate is made of a material having a smaller absorption rate of electromagnetic waves in any band having a wavelength in the range of 0.2 μm or more and 100 μm or less than that of the semiconductor layer; The substrate is formed so as to extend beyond the periphery of the semiconductor layer; the semiconductor layer includes a fibrous carbon nanostructure; A thermoelectric conversion element, characterized in that a junction between the p-type semiconductor region and the n-type semiconductor region of the semiconductor layer is in contact with one main surface of the substrate.
2. 2. The thermoelectric conversion element according to claim 1, wherein the fibrous carbon nanostructure is made of a carbon nanotube.
3. 3. The thermoelectric conversion element according to claim 2, wherein the carbon nanotubes have a diameter of 0.5 nm or more and 15 nm or less.
4. 3. The thermoelectric conversion element according to claim 1, further comprising an i-type semiconductor region at a junction between the p-type semiconductor region and the n-type semiconductor region.
5. 3. The thermoelectric conversion element according to claim 1, wherein the substrate is a flexible substrate.
6. 3. The thermoelectric conversion element according to claim 1, wherein the substrate is made of a material that is capable of transmitting the electromagnetic waves.
7. 3. The thermoelectric conversion element according to claim 1, wherein the substrate is made of a film containing at least one of a polyimide film, a cycloolefin film, and a benzocyclobutene film.
8. 3. The thermoelectric conversion element according to claim 1, wherein the n-type semiconductor region contains a reduction-calcined product of the fibrous carbon nanostructure and an ionic surfactant.
9. 9. The thermoelectric conversion element according to claim 8, wherein the ionic surfactant is an anionic surfactant.
10. A thermoelectric conversion module comprising a plurality of thermoelectric conversion elements according to claim 1 or 2.
11. A wideband image sensor comprising the thermoelectric conversion module according to claim 10 as an imaging element.
12. 3. A method for producing a thermoelectric conversion element according to claim 1 or 2, comprising the steps of: preparing an n-type fibrous carbon nanostructure composition liquid containing the fibrous carbon nanostructure, an ionic surfactant, an n-type semiconductor dopant, and a solvent; and preparing a p-type fibrous carbon nanostructure composition liquid containing the fibrous carbon nanostructure and a solvent. a film-forming step of spreading the n-type fibrous carbon nanostructure composition liquid and the p-type fibrous carbon nanostructure composition liquid on a transfer plate to form a film; a firing step of firing the film-formed body in a reducing atmosphere to obtain the semiconductor layer; a transfer step of transferring the semiconductor layer from the transfer plate to the substrate; A method for manufacturing a thermoelectric conversion element, comprising at least the steps of:
Citation Information
Patent Citations
Filter press
JP1982068299A
Locking device for window, etc.
JP1988040077A